Living Law dan 'Urf sebagai Sumber Hukum Positif di Indonesia - Nafi' Mubarok (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article deals with the issue of living law and 'urf as the sources of positive law in Indonesia. The existence of living law and 'urf (habits which are normally and consistently conducted by members of society) are acknow-ledged in Indonesian legal system. In fact, the theory of living law and 'urf have been adopted as legal reasoning for many laws or bills, such as the law number 23/2014 on local government and the law number 21/2008 on Shariah banking. It can bee seen that many legal decisions by courts judges also have their sources from living laws, such as what deals with criminal sanction, female reciepient of inheritance, the validaty of a merriage. Many legal decisions by court judges also adopt the 'urf, such as the amount of money for 'iddah (waiting time before marriage after divorce), the validity of eloping (kawin lari), shared property in marriage.